Focal genomic amplification at 19q13.42 comprises a powerful diagnostic marker for embryonal tumors with ependymoblastic rosettes - Korshunov, Andrey; Remke, Marc; Gessi, Marco; Ryzhova, Marina; Hielscher, Thomas; Witt, Hendrik; Tobias, Vivienne; Buccoliero, Anna Maria; Sardi, Iacopo; Gardiman, Marina Paola; Bonnin, Jose; Scheithauer, Bernd; et al. (Acta neuropathologica, 2010)
Ependymoblastoma (EBL) and embryonal tumor with abundant neuropil and true rosettes (ETANTR) are very aggressive embryonal neoplasms characterized by the presence of ependymoblastic multilayered rosettes typically occurring in children below 6 years of age. It has not been established whether these two tumors really comprise distinct entities. Earlier, using array-CGH, we identified a unique focal amplification at 19q13.42 in a case of ETANTR. In the present study, we investigated this locus by fluorescence in situ hybridization in 41 tumors, which had morphologically been diagnosed as EBL or ETANTR. Strikingly, FISH analysis revealed 19q13.42 amplifications in 37/40 samples (93%). Among tumors harboring the amplification, 19 samples were identified as ETANTR and 18 as EBL. The three remaining tumors showed a polysomy of chromosome 19. Analysis of recurrent/metastatic tumors (n = 7) showed that the proportion of nuclei carrying the amplification was increased (up to 80-100% of nuclei) in comparison to the corresponding primary tumors. In conclusion, we have identified a hallmark cytogenetic aberration occurring in virtually all embryonal brain tumors with ependymoblastic rosettes suggesting that ETANTR and EBL comprise a single biological entity. FISH analysis of the 19q13.42 locus is a very promising diagnostic tool to identify a subset of primitive neuroectodermal tumors with distinct morphology, biology, and clinical behavior.
Gesehen am 22.03.2023